1997
DOI: 10.1080/016502597384992
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Temperament and Behaviour Problems: A Longitudinal Study from 1.5 to 12 Years

Abstract: Results of a 10-year longitudinal study on the developmental-behavio ural signi cance of infant temperamen tal dif cultness are presented. A cross-time, cross-context methodology was employed using data from over 100 children participating in the Fullerton Longitudinal Study. Dif cult temperament was assessed at 1.5 years by mothers; behaviour problems were assessed by parents during the third year and annually from 4-12 and by teachers from 6-11 years. Temperamental dif cultness correlated signi cantly, perva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(77 citation statements)
references
References 38 publications
5
67
1
4
Order By: Relevance
“…In general population children, temperamental factors are associated with behavior problems [13,16], with fussy-difficult and persistent temperaments being the strongest predictors of behavior problems [15]. Other researchers found that infants with a difficult temperament were three times more likely to be in the clinical range of behavior problems than those without a difficult temperament [17].…”
Section: Introductionmentioning
confidence: 99%
“…In general population children, temperamental factors are associated with behavior problems [13,16], with fussy-difficult and persistent temperaments being the strongest predictors of behavior problems [15]. Other researchers found that infants with a difficult temperament were three times more likely to be in the clinical range of behavior problems than those without a difficult temperament [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Guerin, Gottfried, and Thomas (1997) found that maternal reports of difficult temperament at 1.5 years were related to both parent and teacher reports of behavior problems, including attention and thought problems, in middle childhood.…”
Section: Temperament: Dimensions or Types?mentioning
confidence: 99%
“…Therefore, heterotypic continuity refers to relations between earlier and later behavior that are based upon age-appropriate and logical associations rather than similarities in exact behaviors. For example, several reports describe the relation between a difficult temperament in infancy and externalizing behavior in childhood (e.g., Guerin et al, 1997;Sanson, Smart, Prior, & Oberklaid, 1993). Clearly, external-izing behaviors can take many different forms and are not isomorphic with irritable behavior.…”
Section: Temperament: Predicting Behavior Across Developmentmentioning
confidence: 99%
“…Specific temperament dimensions are associated with distinct combinations of psychobiological substrates. Research has found several temperament traits to have direct, main-effects-type relations with behavior problems in a nonperfect but replicated pattern of partially differential linkage: Temperamental predictors of behavior problems include (a) irritability-difficultness, preceding both internalizing (e.g., anxious) and externalizing (e.g., aggressive) kinds of behavior problems; (b) behavioral inhibition-fearfulness, typically preceding internalizing more so than externalizing problems (but not always); and (c) impulsivity-unmanageability, typically preceding externalizing problems more than internalizing problems Guerin, Gottfried, & Thomas, 1997;Rothbart & Bates, 1998;Sanson, Smart, Prior, & Oberklaid, 1993;Slotboom, Elphick, van Riessen, van Mill, & Kohnstamm, 1996). Details of the process by which temperament predicts later behavior problems are not known, but the evidence so far provides modest support for models of direct (e.g., continuity of personality traits) and indirect (e.g., through child's impact on parents) linear effects (Rothbart & Bates, 1998).…”
mentioning
confidence: 99%